PENERAPAN DESIGN THINKING PADA MEDIA KOMUNIKASI VISUAL PENGENALAN KEHIDUPAN KAMPUS BAGI MAHASISWA BARU STMIK PALCOMTECH DAN POLITEKNIK PALCOMTECH - Syahrul, Yasermi (Jurnal Bahasa Rupa, 2019)
The development of visual communication design has grown and developed and become familiar with human life. Design Thinking is a tool used in problem-solving, problem-design, to problem-forming. Not only resolves a problem, but also for forming and designing a problem. In the process design thinking is human centered or human centered. Every design thinking process originates and is aimed at humans. The application of many design functions is applied in various ways, such as for the education sector, tourism, business and others. The application of design functions in the education sector is like solving problems related to design in order to prepare new students in passing the transition process to become an adult and independent student, as well as to accelerate the process of student adaptation to the new environment and provide provision for success in higher education. Introduction of Campus Life for New Students (PKKMB), visual communication media are needed. The purpose of this study was to design visual communication media about the implementation of PKKMB at STMIK PalComTech and PalComTech Polytechnic in 2018. This study used the Design thinking method. Design Thinking is a user / user focused problem solving method. The stages in design thinking are Emphatize, Define, Ideate, Prototype, and Test. The results obtained from this study are in the form of designs that have been conceptualized well for the implementation of PKKMB at STMIK PalComTech and PalComTech Polytechnic in 2018 in the form of name tag design, back drop design, and banner.